Rebranding Soklat Brew Batang dan Aplikasinya pada Media Promosi - Kurniawan, Dedy; Rahmawati, Anik; Nilda Syah, Naziah (Fakultas Komputer Dan Desain, 2025)
Soklat Brew is a chocolate beverage business formerly known as Chocolate Mas Mboy Semarang. The renaming represents an adaptive strategy in response to the evolving trends of contemporary beverage markets and aims to establish a more modern brand image. However, this name transformation has not yet been supported by a strong visual identity and consistent promotional strategies. This study aims to redesign the visual identity of Soklat Brew Batang using the Robin Landa method, which consists of the stages of orientation, analysis, concept development, design, and implementation. The outcome of this design process includes a new logo, tagline, and a comprehensive visual identity system applied across various promotional media, both digital and print such as packaging, merchandise, social media, and booth displays. All visual elements are compiled into a Graphic Standard Manual to ensure consistent brand application. Through this approach, Soklat Brew is expected to enhance its market competitiveness and broaden its market reach.